Implementing agents for a collaborative online learning environment - Azevedo, Hilton José Silva de (2004)
This paper discusses the main lines used to model intelligent agents that will operate in a Collaborative Online Learning Environment-COLE. The aim of COLE is to evaluate the contribution that Information Technology and Multiagent Systems can bring to the discussion about new adult learning processes. The work hypothesis is that online environments can better handle the huge mass of data related to human interactions in social learning processes than the face-to-face educational ones. Acquiring and managing expanded sets of data has been an obstacle to implement educational practices that consider students in broader dimensions, far beyond content assessment. Elements of the Social Learning Theory, specifically concepts from the Communities of Practice base COLE implementation. A brief description of Project Based Learning - PBL and portfolios (here conceptual maps) give elements to understand the project approach. The SAAS method, used to identify the agents is described. Use cases related to the "Librarian Agent" and the "Portfolio Agent" are presented and windows related to the "portfolio" and "active reading annotation" services illustrate the work.